Mifepristone Treatment in Pregnant Murine Model Induced Mammary Gland Dysplasia and Postpartum Hypogalactia - Zhu, Hongmei; Jia, Xuchen; Ren, Mingli; Yang, Liguo; Chen, Jianguo; Han, Li; Ding, Yi; Ding, Mingxing (Frontiers in Cell and Developmental Biology, 2020)
Mammary gland dysplasia and postpartum hypogalactia often occur in humans and in livestock breeding industry. However, their underlying mechanisms are not clear yet. Mifepristone, which has a high affinity for P4 and glucocorticoid receptors, was exploited here to induce the disorders of mammary gland development and lactation. Four strategies were devised for treating pregnant mice with mifepristone. In the first strategy, mice were administrated with 1.20 mg mifepristone/kg body weight (BW) on pregnancy day 4 (Pd4). In the second strategy, mifepristone was administrated to mice twice, with 1.20 mg/kg BW on Pd4 and 0.40 mg/kg BW on Pd8. In the third strategy, mice were treated with a single dose of 0.40 mg mifepristone/kg BW on Pd8. In the fourth strategy, mice were administrated with 0.40 mg mifepristone/kg BW on Pd8 and 0.20 mg mifepristone/kg BW on Pd12. The results suggested that mifepristone administration at the dose of 1.20 mg/kg BW on Pd4 caused significant reduction in milk production on lactation day 1 (Ld1), Ld2, and Ld3, as assessed using a weigh-suckle-weigh assay. Mammary β-casein expression, milk yields, litters growth rates, gland structure, and serum concentrations of 17-β estrogen (E2), progesterone (P4), prolactin (PRL), growth hormone (GH), corticosterone (CORT) and oxytocin (OT) as well as the receptors of these hormones were determined during pregnancy or lactation after performing the first (Pd4) strategy. The results demonstrated that mifepristone administration during early pregnancy decreased β-casein expression, milk yields and litter growth rates, induced fewer alveoli, enlarged alveolar lumina, and altered the levels of E2, P4, PRL, GH, CORT and OT as well as the mRNA expression of these hormonal receptors during pregnancy or early lactation. The present study on pregnant mice treated with mifepristone offers an innovative murine model to study the mechanism underlying mammary gland dysplasia and postpartum hypogalactia.